Mapping the landscape of positive and negative organizations in innovation implementation - Machado, Diana; Pereira, José; José, Reginalda; Palma-Moreira, Ana; Au-Yong-Oliveira, Manuel (Frontiers in Communication, 2025)
IntroductionThe successful implementation of innovation is a crucial factor in the survival of organizations in a competitive environment. This study aims to analyze how communication practices in positive and negative organizations influence the implementation of innovation, combining a literature review with a bibliometric analysis of international scientific production published between 1997 and 2024.MethodsA total of 132 documents were analyzed, extracted from the Scopus database and processed with the support of VOSviewer software, allowing the identification of publication patterns, authors, and the most relevant journals. The utilization of bibliometric indicators enabled the characterization of the current state of international research.ResultsA review of the literature reveals that organizations that promote a collaborative and transparent work environment tend to be more conducive to innovation. Conversely, organizations characterized by internal conflicts and resistance to change can act as obstacles to innovation. According to a bibliometric analysis, the results show a growing academic interest in this field, with a greater production of articles in recent decades. The literature review identifies gaps in the literature, indicating a need for further empirical studies that examine the relationship between positive and negative organizations and the implementation of innovation.DiscussionThis study contributes to the literature on organizational communication by highlighting the central role of internal communication in promoting positive and innovative organizational environments, offering useful recommendations for professionals who wish to drive innovation in their organizations.